FORMULASI LIP BALM EKSTRAK LIDAH BUAYA (ALOE VERA) DAN BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) SEBAGAI PELEMBAB BIBIR - Tampubolon, Antetti (Jurnal Riset Kefarmasian Indonesia, 2023)
Lip balm is a cosmetic preparation with main components such as waxes, fats and oils. The purpose of this study was to determine whether Aloe vera and red dragon fruit extracts could be formulated as moisturizers and natural dyes in lip balm preparations. The study was carried out experimentally, including the formulation of preparations with concentrations of Aloe Vera extract 3%, 6%, 10%, and Red Dragon Fruit extract 3%, 5%, 7%. Examination of the physical quality of the preparation, namely homogeneity test, stability during 28 days of storage at room temperature, melting point, pH, and preference test. The results showed that (F1) with a concentration of 3% aloe vera and 3% red dragon fruit met the requirements for homogeneity, melting point, pH, and stability tests, on (F2) with a concentration of 6% aloe vera and 5% red dragon fruit does not meet the requirements of the pH test, but meets the requirements of the homogeneity test, melting point test, and stability test. Whereas for (F3) with a concentration of 10% aloe vera and 7% red dragon fruit did not meet the homogeneity and pH test requirements, but met the melting point and stability test requirements. It can be concluded that Aloe Vera Extract and Red Dragon Fruit can be formulated into lip balm dosage forms. Differences in concentration variations can affect the moisture on the skin and the color of the preparation.